TWO USM LECTURERS RECEIVE MAKNA CANCER RESEARCH AWARD 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 29 April 2017 Two budding young lecturers from Universiti Sains Malaysia (USM), Associate Professor Dr. Asrul Akmal Shafie (School of Pharmaceutical Sciences) and Dr. Oon Chern Ein (Institute for Research in Molecular Medicine/INFORMM) have put the name of the university in the limelight once again, when they were selected for the MAKNA Cancer Research Award 2016, held recently at the Academy of Sciences Malaysia (ASM), MATRADE Tower, Kuala Lumpur.